Somatostatin attenuates intestinal epithelial barrier injury during acute intestinal ischemia–reperfusion through Tollip/Myeloiddifferentiationfactor 88/Nuclear factor kappa-B signaling. Issue 3 (1st March 2022) - Tian, Yan; Shu, Ruo; Lei, Yi; Xu, Yu; Zhang, Xinfeng; Luo, Huayou
ABSTRACT: In the process of ischemia–reperfusion injury, intestinal ischemia and inflammation interweave, leading to tissue damage or necrosis. However, oxygen radicals and inflammatory mediators produced after reperfusion cause tissue damage again, resulting in severe intestinal epithelial barrier dysfunction. The aim of this study was to determine the protective effect of somatostatin on intestinal epithelial barrier function during intestinal ischemia–reperfusion injury and explore its mechanism. By establishing a rat intestinal ischemia–reperfusion model, pretreating the rats with somatostatin, and then detecting the histopathological changes, intestinal permeability and expression of tight junction proteins in intestinal tissues, the protective effect of somatostatin on the intestinal epithelial barrier was measured in vivo. The mechanism was determined in interferon γ (IFN-γ)-treated Caco-2 cells in vitro. The results showed that somatostatin could ameliorate ischemia–reperfusion-induced intestinal epithelial barrier dysfunction and protect Caco-2 cells against IFN-γ-induced decreases in tight junction protein expression and increases in monolayer cell permeability. The expression of Tollip was upregulated by somatostatin both in ischemia–reperfusion rats and IFN-γ-treated Caco-2 cells, while the activation of TLR2/MyD88/NF-κB signaling was inhibited by somatostatin. Tollip inhibition reversed the protective effect of somatostatin on the intestinal epithelial barrier. In conclusion, somatostatin could attenuate ischemia–reperfusion-induced intestinal epithelial barrier injury by inhibiting the activation of TLR2/MyD88/NF-κB signaling through upregulation of Tollip. Graphical abstract: uf0001